Penerapan Pijat Refleksi Kaki Terhadap Tekanan Darah pada Pasien Hipertensi di Ruang Teratai 3 RSUD Kartini Karanganyar - Ema Erfiana; Fida' Husain; Dewi Listyorini (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Hypertension is a disease that can be experienced by various groups of people from high to lower middle social levels, from teenagers to the elderly where this condition experiences an increase in blood pressure from normal conditions (130/80 mmHg). One non-pharmacological intervention, namely foot reflexology, is an option because this action is safe for patients because it is not invasive and is easy to do by traffic. Foot reflexology massage is able to improve blood flow, the nerve points of the feet are massaged and have a relaxing effect on the body. Foot massage has a mechanical effect of improving blood circulation so it can lower blood pressure. To determine the results of applying foot reflexology massage on blood pressure in hypertensive patients at Karanganyar Regional Using a descriptive method in the form of a case study for 2 patients with hypertension. Respondent 1 before applying foot reflexology massage found blood pressure from 176/100 mmHg to 165/90 mmHg. Meanwhile, Respondent 2 before applying foot reflexology massage found that his blood pressure was 150/90 to 143/80. Foot reflexology massage can be used as a non-pharmacological technique to reduce blood pressure in hypertension patients.